Thai Undergraduate Students’ Feedback Preference and Motivation in Learning Chinese as a Foreign Language in Thailand - Srisinthon, Pairin; Jifeng, Yuan (Journal of Education Culture and Society, 2026)
Aim. This study aims to examine the intersection of learning feedback and student motivation in the context of Chinese as a Foreign Language (CFL) education within Thai higher education institutions, an area with limited prior research.Methods. Employing a mixed-method design and convenient sampling, 215 Chinese major students at an autonomous Thai institution participated. Data was collected through questionnaires and semi-structured interviews. Confirmatory Factor Analysis (CFA) was conducted to validate the measurement model (χ²/df=2.07, CFI=.932$, TLI=.924, RMSEA=.083, SRMR=.048). The regression analysis was used to examine the relationships between learning feedback and student motivation. Furthermore, thematic analysis was utilised to identify and extract themes from the interview data.Result. The results demonstrated a strong preference among students for corrective feedback and feedback provided by their teachers, with lower-year students exhibiting a greater feedback preference. Advanced academic-year students displayed a propensity to engage critically with feedback, fostering self-reliant learning skills. Learning feedback significantly and positively predicted motivation. Regression analysis showed that this relationship was consistent across academic years. Conclusions. The findings highlight the motivational significance of structured and informative instructional feedback in foreign language education. This study emphasises the crucial role of teachers in delivering feedback and fostering an environment conducive to active learning, emphasising the need for both educators and students to understand and effectively utilise feedback to enhance learning outcomes. Additionally, the findings revealed that Thai undergraduate students' motivation stemmed from their desire to build meaningful social connections with those who value the CFL and recognise its relevance for future career prospects.